Structural, Optical and Electrochromic Properties of Nanocrystalline TiO2 Thin Films Prepared by Spin Coating - R. Jourdani; A. Outzourhit; A. Oueriagli; D. Aitelhabti; E. L. Ameziane; S. Barazzouk; S. Hotchandani (Active and Passive Electronic Components)
Nanocrystalline TiO2 thin filmswere prepared by spin coating on covered glass substrates with an indium tin oxide (ITO) layer. The structural, electrochromic and optical properties of the films were investigated. The films are crystallized predominantly in the anatase phase with lattice parameters a = b = 0.378 nm and c = 0.958 nm . The crystallite size was found to be of the order of 14 nm. The films showed reversible coloration/bleaching cycles as demonstrated by cyclic voltametry and current–time transients. The transmission of the blue colored films decreased and their absorption edge was less sharp and shifted to higher wavelengths as a result of the intercalation of Li+ ions.